Prevalence, Characteristics, and Selection of Bacillus cereus Subgroups from Dairy Products for Challenge Testing and Predictive Model Development - Maryam Maktabdar; Lisbeth Truelstrup Hansen; Ellen Wemmenhove; Elissavet Gkogka; Paw Dalgaard (Journal of Food Protection)
Prevalence, toxin gene profiles, lactose fermentation, and growth responses of B. cereus sensu lato subgroups in various dairy and dairy alternative products and ingredients were studied to identify relevant isolates for challenge testing and model development to predict and manage growth responses. Out of 71 examined products or ingredients, 51 B. cereus s.l. isolates were obtained from 35 positive samples (49% prevalence). These 51 isolates along with 18 additional dairy isolates and 12 B. cereus s.l. reference strains were identified using MALDI-TOF. The 81 isolates were further characterized by panC sequencing, testing for cold shock and toxin genes (cspA; hbl, nhe, CytK and ces), lactose fermentation, and study of growth rates (µmax) under various conditions (45 °C, 10 °C, 6% NaCl, pH 5.1), resulting in 298 µmax-values. These conditions were selected to differentiate mesophilic and psychrotolerant strains and to identify tolerant isolates. Dairy powders (83%), pasteurized upconcentrated cheese whey (43%), and cheeses (42%) had the highest prevalences of B. cereus s.l. and the highest concentrations in positive samples (5–100 CFU/g or ml). The panC groups II, III, IV, VI, and VIII were detected among the dairy isolates, with 97% harboring one or more toxin genes. Lactose fermentation was observed in 42% of isolates, with lactose-fermenting B. cereus s.l. isolates of panC groups III and IV dominant in dairy powders. Growth rates of B. cereus s.l. varied considerably, among and within panC groups of the dairy isolates. Based on the highest growth rates at 45 °C, 10 °C, 6% NaCl, pH 5.1, panC group membership, toxin genes profiles, and lactose fermentation ability, two cocktails of “mesophilic” or “psychrotolerant” isolates were selected. These strain cocktails can be used in future challenge testing and predictive food microbiology studies to evaluate and manage the growth of B. cereus s.l. in dairy products and ingredients.